2019
DOI: 10.1002/dmrr.3247
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth and telemedicine applications for the diabetic foot: A systematic review

Abstract: Summary The aim of this systematic review is to assess the peer‐reviewed literature on the psychometric properties, feasibility, effectiveness, costs, and current limitations of using telehealth and telemedicine approaches for prevention and management of diabetic foot disease. MEDLINE/PubMed was searched for peer‐reviewed studies on telehealth and telemedicine approaches for assessing, monitoring, preventing, or treating diabetic foot disease. Four modalities were formulated: dermal thermography, hyperspectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 89 publications
(314 reference statements)
0
68
0
6
Order By: Relevance
“…This allows simultaneous measurements of temperature, plantar pressure, and toes range of motion, which makes it suitable for objectively assessing lower extremity regions at risk. The authors of this work found a moderate agreement in foot temperature changes between SmartSox and an infrared thermal camera [153].…”
Section: Biomedical Optical Fiber Temperature Sensorsmentioning
confidence: 61%
“…This allows simultaneous measurements of temperature, plantar pressure, and toes range of motion, which makes it suitable for objectively assessing lower extremity regions at risk. The authors of this work found a moderate agreement in foot temperature changes between SmartSox and an infrared thermal camera [153].…”
Section: Biomedical Optical Fiber Temperature Sensorsmentioning
confidence: 61%
“…Additionally, there was no significant cost reduction for the group receiving telemedicine care [ 33 ]. In subsequent studies, specific factors that were critical to effective diabetic foot telecare were identified: technology and training, user-friendliness, people in charge who facilitate the intervention, the need for support from leaders, as well as appropriate communication at the structural level [ 34 , 35 ].…”
Section: Available Telediabetology Solutionsmentioning
confidence: 99%
“…Also, lengthening of our study could not be justified, since we had to overthrow our hypothesis of a positive association between plantar foot thermal asymmetry and clinical assessment of DFI severity after analyzing the initially obtained data. In retrospect, more patients could have been included if we would have used more straightforward and practical mobile phone applications for thermographic assessment in a multicenter setting (29,30,31), but these were not available at the time. Even though a statistical significant result was unlikely to be obtained due to the low number of included patients, the initial findings are highly indicative of our hypothesis being incorrect.…”
Section: Discussionmentioning
confidence: 99%